A case study of how education labour markets are organized in Japan: mandatory teacher rotation in Japanese public schools. Issue 3 (3rd July 2019) - Seebruck, Ryan
ABSTRACT: Public teachers in Japan are subjected to a compulsory rotation system where the prefectural board of education governs their entire career paths. Past research has written of the macro- and micro-level impacts of rotation systems, including Japanese teacher rotation, but this paper, based on years of working in and observing Japanese schools, is the first study in English to offer a detailed examination of how the system functions, revealing how informal and formal organizational structure work in concert to facilitate teacher rotation in Japan.